Organizational and legal contexts of digital-security tools of economic agents - Vivchar, Oksana; Chudyk, Nataliia (Актуальні проблеми правознавства, 2022)
The article examines the organizational and legal apparatus «digitalization» and the algorithm of the digitalization process of economic agents in the context of security conditions. A practical toolkit of methods and algorithms (SADT, IDEF, UML, BPMN) that provide automation of work flow management using web technologies is substantiated. As a result of scientific research, the main vectors of ensuring the safety of economic agents in modern conditions of digitalization of economic processes have been identified. On the basis of which, the organizational and legal foundations of the implementation of digital processes on the state and development possibilities of strengthening the security of economic agents are characterized. The peculiarities of providing the appropriate security components in the conditions of active processes of digitalization of economic and legal relations have been studied